Translation and validation of the Parent-adolescent Communication Scale: technology for DST/HIV prevention (Revista Latino-Americana de Enfermagem, 2013)
OBJECTIVES: accomplishment of the transcultural adaptation of the Parent-adolescent Communication Scale, which evaluates the frequency of communication between parents and children concerning the subjects related to sex, condom, DST, HIV and pregnancy. METHOD: Methodological research of quantitative approach, accomplished with 313 adolescent pupils of the feminine sex in the 14 to 18 year age group in Fortaleza-CE. The content validity was carried through by means of the initial translation, back translation, pre-final version and final version, being analyzed by a committee of specialists; the reliability was verified by the Cronbach's Alpha and ascertained by testing the hypotheses and test-retest within five weeks. The scale was applied via computer in the online modality in the period November/2010 to January/2011. RESULTS: The version of the instrument in Portuguese presented an Alpha of 0.86 regarding the validity of the structure, was partially verified since the testing of the hypotheses of the contracted group was not confirmed. CONCLUSION: The version of the instrument adapted for Portuguese is considered valid and reliable in the study sample.